PENERAPAN MODEL PEMBELAJARAN COOPERATIVE LEARNING TIPE JIGSAW PADA MATA PELAJARAN PAI MATERI AKHLAK DALAM MENINGKATKAN HASIL BELAJAR SISWA (STUDI EKSPERIMEN DI SMA NEGERI 1 TANAH ABANG KABUPATEN MUARA ENIM) - Nia Anggraini; Ismail Sukardi (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2011)
The research experiment was conducted in SMA 1 Tanah Abang Muara Enim District. This research was aimed at finding out the differences in student learning outcomes of PAI subject in the control class before and after the treatment, as well as the difference between student learning outcomes in PAI subject in the experimental class (which are taught by using of type Jigsaw cooperative learning models) while in the control class students are not taught by using Jigsaw cooperative learning Model). The research was located at SMA Negeri 1 Tanah Abang. The sampling of this study, was simply taken from students of class IX Science 2 as a control class which consists of 30 students and class class IX science 1 as experiment class which consists of 35 students based on proportional sampling. The total sample was 65 students. To get the data, the writers conducted experiments on the control and experimental class by giving the test. So the method used was experimental method, test, observation, and documentation. While, the analytical technique used is the formula